Pertanggung jawaban Direksi Perseroan Perorangan Terhadap Pemenuhan Ganti Kerugian - Muhimmatul Hidayah; Sumriyah Sumriyah (Jurnal Relasi Publik, 2024)
This research aims to determine the direction of limited liability companies in related regulations and laws. This research is a normative juridical research which is a research that examines all regulations and laws relating to the problem. The data used is secondary data which is divided into primary and secondary legal materials. The problems of this research are two problems, namely what is the legal position in fulfilling compensation incurred by directors of individual companies and what is the responsibility of directors of individual companies in the case of individual companies that have experienced losses. The results of this research are directions for individual corporations to be required to compensate for losses caused by actions or carelessness that violate the law or obligations and the Board of Directors offers supervision relating to company management policies and the company's business activities.